The Potential Role of Circulating Endothelial Cells and Endothelial Progenitor Cells in the Prediction of Left Ventricular Hypertrophy in Hypertensive Patients - Budzyń, Magdalena; Gryszczyńka, Bogna; Boruczkowski, Maciej; Kaczmarek, Mariusz; Begier-Krasińska, Beata; Osińska, Angelika; Bukowska, Alicja; Iskra, Maria; Kasprzak, Magdalena Paulina (Frontiers in Physiology, 2019)
Background: The main aim of present study was to evaluate the potential role of circulating endothelial cells (CECs) and endothelial progenitor cells (CEPCs) - representing specific markers of endothelial damage, in the prediction of left ventricular hypertrophy (LVH) in hypertensive patients categorized into two groups, mild (MH) and resistant hypertension (RH). Materials and methods: 30 patients with MH and 28 subjects with RH were involved in the study. In both groups, patients were divided into LVH and non-LVH group. The control group included 33 age and sex-matched normotensive volunteers. Physical examination, laboratory tests and echocardiography were conducted. Results: In both, MH and RH group, patients with as well as without LVH demonstrated a higher number of CECs and a lower ratio of CEPCs/CECs as compared to healthy control. Multiple linear regression analysis showed a positive association of CEPCs with left ventricular mass (LVM) and left ventricular mass index (LVMI), independently of other confounders. Conclusions: Our results suggest that endothelial injury observed as an elevated CECs number and its impaired regeneration reflected by a lowered CEPCs/CECs ratio precede LVH occurrence and may play a significant role in LVH development, regardless of the clinical severity of hypertension. Moreover, independent correlation of CEPCs with echocardiographic (ECG) incidences of LVH suggests their potentially use as a screening biomarker to stratify risk of LVH development.